Optimalizace provozu čistíren odpadních vod - Singrová, Veronika (Vysoké učení technické v Brně. Fakulta stavební, 2019)
Cílem diplomové práce je posouzení dvou vybraných čistíren odpadních vod a návrh vhodných opatření souvisejících s optimalizací provozu. Čistírny jsou z Jihomoravského a Zlínského kraje a obě spadají do kategorie 2 001 – 10 000 EO. V práci se objevuje posouzení stavebních objektů, strojního zařízení, účinnosti čištění a energetické náročnosti obou ČOV. Výpočty vycházejí z reálně měřených veličin za poslední tři roky a ze základních parametrů jednotlivých objektů a zařízení. Je tedy shrnutý nynější skutečný stav obou čistíren a návrhy na jejich optimalizaci jsou seřazeny dle důležitosti.

The aim of this diploma thesis is to evaluate two selected wastewater treatment plants and to propose appropriate measures related to optimization of operation. Wastewater treatment plants are from the Jihomoravský and Zlínský regions and both come under the category 2 001 - 10 000 equivalent inhabitants. In the diploma thesis there is an assessment of construction objects, machinery, cleaning efficiency and energy performance of both WWTPs. The calculations are based on the real measured values for the last three years and on the basic parameters of individual objects and equipment. The present state of the two wastewater treatment plants is summarized and optimization proposals are sorted by importance.
Optimizing the operation of wastewater treatment plants
Keywords: Čistírna odpadních vod; optimalizace provozu; energetická náročnost; posouzení objektů a zařízení; emisní standardy.; Wastewater treatment plant; optimizing the operation; energy performance; assessment of objects and equipment; emission standards.